Epstein-Barr Virus in Biopsies from Patients with Hodgkin and Non-Hodgkin Lymphoma at the University of Puerto Rico Immunohistochemistry Laboratory - Córdova-Pérez, Francisco J.; González-Keelan, Carmen I.; Vélez, Román (Puerto Rico Health Sciences Journal, 2011)
see manuscript